СОСТАВЛЕНИЕ АНКЕТ ДЛЯ ИЗУЧЕНИЯ НЕРАВЕНСТВА В ОБЩЕСТВЕ, ИХ АНАЛИЗ И ОБРАБОТКА - Шмерлинг, Дмитрий; Великая, Елена; Нелюбина, Иванна; Иналишвилы, Майя (Modern scientific researches, 2019)
Methods of mathematical statistics (MS), which encompass econometrics (E) as well, cannot solve all the socio-economic problems. This work attempts to cast light on applying to expert judgements (EJ) when handling socio-economic tasks (SE). In order to ca